Market Segmentation in Marketing for Socio-economic Vulnerable Women Micro Business Actor in Sumedang Regency - Diana Diana (International Seminar on Social Work Update, 2023)
Market segmentation is an attempt to classify market groups from heterogeneous markets into homogeneous market parts. The research aimed to obtain an in-depth description of: 1) Profile of PRSE Micro Enterprises 2) Market segmentation of PRSE micro enterprises in Kota Kulon Village, South Sumedang Sub-district, Sumedang Regency, 3) Steps in market segmentation. The method used in this study is descriptive qualitative with primary and secondary data sources. Data collection techniques used in-depth interviews, observation, and documentation studies. The results of the study show that PRSE micro-entrepreneurs in Kota Kulon Village sort markets based on demographic, geographic and behavioral segments. Demographic segment variables were selected based on gender and school age. The behavioral segment variable was selected based on the incident where the goods being sold were food to meet the needs of people who wanted to be practical by buying food for breakfast early in the morning, and selling pastries only just before Idul Fitri. The variable chosen is in the geographical segment, this business provides goods only for the area around the shop. The steps taken in determining market segmentation are to collect information from consumers who come when shopping so that this business can study the characteristics of each segment which has an impact on increasing sales of its goods so that the basic needs of PRSE are met